Controlled Peptide-Mediated Vesicle Fusion Assessed by Simultaneous Dual-Colour Time-Lapsed Fluorescence Microscopy - Mora, Nestor Lopez; Boyle, Aimee L; Kolck, Bart Jan van; Rossen, Anouk; Pokorná, Šárka; Koukalová, Alena; Šachl, Radek; Hof, Martin; Kros, Alexander (Scientific reports, 2020)
We have employed a model system, inspired by SNARE proteins, to facilitate membrane fusion between Giant Unilamellar Vesicles (GUVs) and Large Unilamellar Vesicles (LUVs) under physiological conditions. In this system, two synthetic lipopeptide constructs comprising the coiled-coil heterodimer-forming peptides K4, (KIAALKE)4, or E4, (EIAALEK)4, a PEG spacer of variable length, and a cholesterol moiety to anchor the peptides into the liposome membrane replace the natural SNARE proteins. GUVs are functionalized with one of the lipopeptide constructs and the fusion process is triggered by adding LUVs bearing the complementary lipopeptide. Dual-colour time lapse fluorescence microscopy was used to visualize lipid- and content-mixing. Using conventional confocal microscopy, lipid mixing was observed on the lipid bilayer of individual GUVs. In addition to lipid-mixing, content-mixing assays showed a low efficiency due to clustering of K4-functionalized LUVs on the GUVs target membranes. We showed that, through the use of the non-ionic surfactant Tween 20, content-mixing between GUVs and LUVs could be improved, meaning this system has the potential to be employed for drug delivery in biological systems.
Keywords: Lipopeptides; Dimerization; cholesterol; Microscopy, Fluorescence; barva; Membrane Fusion; Polysorbates; lipidy; Unilamellar Liposomes; dimerizace; unilamelární lipozómy; Color; Lipids; fluorescenční mikroskopie; fluorescenční spektrometrie; Cholesterol; fúze membrán; lipopeptidy; peptidy; polysorbáty; Fluorescence Resonance Energy Transfer; Microscopy, Confocal; konfokální mikroskopie; Spectrometry, Fluorescence; rezonanční přenos fluorescenční energie; Peptides